2006
DOI: 10.1182/blood-2005-08-027979
|View full text |Cite
|
Sign up to set email alerts
|

Deficient expression of NCR in NK cells from acute myeloid leukemia: evolution during leukemia treatment and impact of leukemia cells in NCRdull phenotype induction

Abstract: Natural killer (NK) cells play an important

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
315
3
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(340 citation statements)
references
References 27 publications
(37 reference statements)
18
315
3
4
Order By: Relevance
“…The majority of AML patients have a downregulated NK cell surface expression of the activating natural cytotoxicity receptors (NCRs; that is, NKp30, NKp44 and NKp46). [24][25][26] Recently, also the expression of DNAX accessory molecule-1 (DNAM-1) was shown to be reduced on NK cells from AML patients younger than 65 years compared with age-matched controls. 27 Together with the activating NK cell receptor NKG2D, these are the main receptors involved in NK cell-mediated recognition and killing of leukemic target cells.…”
Section: How Aml Evades Nk Cell Immune Surveillancementioning
confidence: 99%
See 2 more Smart Citations
“…The majority of AML patients have a downregulated NK cell surface expression of the activating natural cytotoxicity receptors (NCRs; that is, NKp30, NKp44 and NKp46). [24][25][26] Recently, also the expression of DNAX accessory molecule-1 (DNAM-1) was shown to be reduced on NK cells from AML patients younger than 65 years compared with age-matched controls. 27 Together with the activating NK cell receptor NKG2D, these are the main receptors involved in NK cell-mediated recognition and killing of leukemic target cells.…”
Section: How Aml Evades Nk Cell Immune Surveillancementioning
confidence: 99%
“…28 Importantly, NCR downregulation (NCR dull ) on NK cells was found to be associated with poor prognosis for AML patients, as NCR dull AML patients showed significantly lower 5-year survival rates than their NCR bright counterparts. 25 Besides the activating receptor status, the inhibitory receptor phenotype also has a role in the escape of AML from NK cells. KIRs are a major NK cell receptor family with important inhibitory potential.…”
Section: How Aml Evades Nk Cell Immune Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…25 Moreover, it has been shown that the down-regulation of NCRs is common in AML and that this phenomenon may lead to defective anti-leukemic response. 26,27 In this study, we ex-vivo explored the function of early reconstituted NK cells following non-haploidentical HSCT. We show for the first time that NK degranulation may fluctuate between day 30 (D30) and day 60 (D60), undergoing a significant down-regulation specific to AML patients at D60.…”
Section: Introductionmentioning
confidence: 99%
“…8 AML blasts can escape NK cell-mediated lytic activity through an extensive process of immune-editing, in which multiple NK cell activation receptors and their ligands are manipulated to inhibit NK cell function (conjugation, degranulation and tumor cell lysis), leading to the induction of NK cell tolerance. 9 Examples of such immune evasion tactics include a dull NCR profile through downregulation of NKp30 and NKp44, 10 loss of NKG2D ligand expression (MICA/B, ULBPs) 11 and perturbation of the DNAM-1-CD112/CD155 axis by inducing downregulation of DNAM-1 expression on NK cells. 12 Therefore, compounds that can increase the activity of NK cells toward AML are of considerable therapeutic interest.…”
Section: Introductionmentioning
confidence: 99%